2009
DOI: 10.1002/stem.153
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Pretreated with Delivered Hph-1-Hsp70 Protein Are Protected from Hypoxia-Mediated Cell Death and Rescue Heart Functions from Myocardial Injury

Abstract: Mesenchymal stem cell (MSC) therapy for myocardial injury has inherent limitations due to the poor viability of MSCs after cell transplantation. In this study, we directly delivered Hsp70, a protein with protective functions against stress, into MSCs, using the Hph-1 protein transduction domain ex vivo for high transfection efficiency and low cytotoxicity. Compared to control MSCs in in vitro hypoxic conditions, MSCs delivered with Hph-1-Hsp70 (Hph-1-Hsp70-MSCs) displayed higher viability and anti-apoptotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 32 publications
2
60
0
1
Order By: Relevance
“…Yield was 3 × 10 6 cells (95% purity) after 2 wk of culture. Consistent with a previous report, the cultured MSCs expressed CD71, CD90, CD105, CD106, and ICAM-1, but not the hematopoietic and macrophage markers, CD34 and CD14, respectively (7,8).…”
Section: Msc Therapy Is Insufficient For Prevention Of Sudden Death Insupporting
confidence: 91%
See 2 more Smart Citations
“…Yield was 3 × 10 6 cells (95% purity) after 2 wk of culture. Consistent with a previous report, the cultured MSCs expressed CD71, CD90, CD105, CD106, and ICAM-1, but not the hematopoietic and macrophage markers, CD34 and CD14, respectively (7,8).…”
Section: Msc Therapy Is Insufficient For Prevention Of Sudden Death Insupporting
confidence: 91%
“…Although preconditioning of MSCs, including genetic modification, has increased their therapeutic potency (6)(7)(8)20), the most obvious concern for clinical applications is how engrafted MSCs electromechanically integrate with host tissue (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2). In mammalian cells, the induction of Hsp70 is HIF-1 dependent, and it was shown that this chaperone has a role in protection against hypoxia injury in tumor, renal, neuronal, and even mesenchymal stem cells (4,7,20,32,35,36,39,46,51). Induction of Hsp70 under hypoxia was also reported to occur in C. albicans (43) and C. neoformans (9).…”
mentioning
confidence: 99%
“…The use of animals was in accordance with the International Guide for the Care and Use of Laboratory Animals. Rat MSCs were harvested and propagated as described previously Chang et al, 2009). Briefly, the rat bone marrowderived cells were flushed out from femurs and tibias with culture medium (DMEM with 10% FBS).…”
Section: Methodsmentioning
confidence: 99%